Interactions between contact lenses and lens care solutions: Influence in optical properties - Alves, Micael (2021)
Purpose: Investigate changes in optical properties of contact lenses materials (transmittance and reflectance) and lens care solutions (absorption and fluorescence) resulting from its interaction. Methods: From an experimental study, triplicate measurements of transmittance and reflectance of five contact lenses (Senofilcon A, Lotrafilcon B, Balafilcon A, Comfilcon A, and Omafilcon A), as well as UV-vis absorption and fluorescence of four lens care solutions (LCS) (ReNu MultiPlus, Biotrue, OPTI-FREE PureMoist, and AOSept Plus), were evaluated before and after 8 h, one day and one week in storage. The outcomes were provided by Shimadzu UV3101-PC UV-vis-NIR spectrophotometer equipped with an integrating sphere, between 200-700 nm, and SPEX-Fluorolog 2 FL3-22 spectrofluorometer. Results: All variables exhibited statistically significant differences over time. Comfilcon A showed the lowest ultraviolet radiation (UVR) A & B attenuation. Balafilcon A and Lotrafilcon B displayed a slight suppression of UVR. Senofilcon A was effective in UVR protection and showed less effect on the fluorescence of lens care solutions. Overall, the reflectance decreased after storage (p < 0.05). AOSept Plus absorbance and fluorescence demonstrated lower interactions than multipurpose solutions (MPS), and Lotrafilcon B induced more remarkable changes in optical properties of LCS than the other materials. Conclusion: The findings suggest that optical variables of lens care solutions and contact lenses changed mutually after storage, probably associated with biochemical and biophysical interactions between components and the release of some polymer compounds. These findings can provide additional information about the interaction of CL materials and LCS in clinical behavior.